2011
DOI: 10.1111/j.1524-4725.2011.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Melanomas: Identification of Factors Associated with Delayed Detection in an Academic Group Practice

Abstract: The increase in melanoma diagnoses was largely due to increases in cases of lentigo maligna on the head and neck. Delayed detection was associated with location on trunk and extremities, new patient status, patient concern before biopsy, and physician suspicion of nonmelanoma skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Several studies have indirectly addressed this question by comparing the frequency with which melanomas are associated with the remnants of banal nevi versus the remnants dysplastic nevi. 64,297301 These analyses have generally shown that dysplastic nevi tend to be associated with melanomas at similar rates as banal nevi, however, this observation may be confounded by the relative abundance of banal nevi relative to dysplastic nevi. 294,295 …”
Section: Dysplastic Nevimentioning
confidence: 99%
“…Several studies have indirectly addressed this question by comparing the frequency with which melanomas are associated with the remnants of banal nevi versus the remnants dysplastic nevi. 64,297301 These analyses have generally shown that dysplastic nevi tend to be associated with melanomas at similar rates as banal nevi, however, this observation may be confounded by the relative abundance of banal nevi relative to dysplastic nevi. 294,295 …”
Section: Dysplastic Nevimentioning
confidence: 99%
“…Bevona et al 119 reported that of 1606 nevus-associated melanomas, 43% arose from DN and 57% from CN. In a review of melanomas diagnosed in an academic group practice over 10 years, Goodson et al 120 reported that 66 melanomas arose from CN versus 45 from DN. Similarly, in several studies of patients with nevi monitored by photography, nevus-derived melanomas appear to arise from DN and CN in roughly equivalent proportions.…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…For example, melanoma may arise de novo at the site of a preexisting nevus, melanoma may create a growth environment in which benign melanocytic proliferations occur more frequently, or melanoma in situ at the border of a neoplastic lesion may be misinterpreted as a nevus . Furthermore, a 10‐year observational study found that 81% of 572 melanomas occurred de novo, and most melanomas associated with a nevus were associated with a common, rather than a dysplastic, nevus . These studies do not establish DN as precursors to melanoma, and in their recent review of DN, Duffy and Grossman concluded that histologic studies suggest that “There is no evidence that individual DN will inevitably progress through sequentially higher grades of dysplasia.…”
Section: Discussionmentioning
confidence: 98%
“…21,27 Furthermore, a 10-year observational study found that 81% of 572 melanomas occurred de novo, and most melanomas associated with a nevus were associated with a common, rather than a dysplastic, nevus. 28 These studies do not establish DN as precursors to melanoma, and in their recent review of DN, Duffy and Grossman concluded that histologic studies suggest that "There is no evidence that individual DN will inevitably progress through sequentially higher grades of dysplasia. There is substantial clinical evidence indicating that melanoma most commonly develops de novo.…”
Section: Discussionmentioning
confidence: 99%